Problematika Hukum Internasional Dalam Kebijakan Deportasi Pengungsi Rohingya Di Indonesia: Analisis Kritis Prinsip Non-Refoulement - Ibnu Mardiyanto (CV. ULIL ALBAB CORP, 2024)
At the end of 2023, Indonesia faced a wave of Rohingya arrivals, who were suspected to be illegal immigrants rather than refugees. This situation was partly triggered by the deteriorating security conditions in the Cox's Bazaar refugee camps in Bangladesh, where thousands of Rohingya refugees were living in increasingly unsafe conditions. Human traffickers exploited this situation by offering dangerous journeys to Indonesia as an alternative. Their arrival created new tensions in the Aceh region, where some local residents expressed rejection. This research aims to analyze Indonesia's deportation policy towards Rohingya refugees at the end of 2023 and examine the legal basis that allows Indonesia to bypass the principle, particularly Article 33(2) of the 1951 Refugee Convention, in order to protect national security. This study employs a normative-empirical legal method, combining textual regulation analysis with empirical data from public responses. The findings of this research show that Indonesia's deportation policy towards Rohingya refugees potentially violates the non-refoulement principle and contradicts the obligation to fulfill human rights. However, there is a legal basis that could justify Indonesia's disregard of the principle. This conclusion is important as it highlights that, despite the limitations in applying the non-refoulement principle, Indonesia must carefully balance national interests with humanitarian responsibilities under international law.